(3fRgI GdCHUGQ aj eMGSf GdCTYGQs - (3GdHgGA RgjQ , RgjQ Hf eMeO Hf Ydj GdegdHj GdUGdMj, HgGA GdOjf,J (B656 (3g` s
(3ChdgG (B:s
(3CeG HYO CeQJ CYdi Gddg CeQc aCLHJc Edi Edjg CTQJ s
(3BNQgG (B:s
(3aGdhLfI YfOejg Yf Oeg JUOjb cdGe gPG BNQ eG hLOJg ef gPG GdcJGH s
(3HChdgG Jedc eDQN SfI (B1166(3g``s
(3HgG fXGe GdJYbjHIs
(3Cdag ddCejQ TLGY GdOjf hbSeg Ydi SHYI CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B136 s
Keywords: (3GdCOHs